Experimental Evaluation of Temperature and Optical Power Generated by a LED Therapy Device on an Agar Phantom - Durmus, Huseyin Okan; Ari, Emel Cetin; Karaboce, Baki; Seyidov, MirHasan Yu (IEEE, 2022)
In this study, we experimentally investigated the effects of temperature and optical power of an LED therapy device within a tissue phantom and on its surface. We attempted to ascertain the effects of LED lights of different colors, such as red, yellow, green, blue, orange, and purple, situated at the LED therapy device on the surface and within the agar phantom. We formed a temperature effect on the agar phantom via the LED therapy device at 20, 40, and 60 minutes intervals. The temperature measurements were performed using a thermocouple placed at the surface and within the agar phantom. Furthermore, the relationships between the obtained internal temperatures of each LED light of different colors and the determined surface temperatures of each LED light of different colors were statistically analyzed, discussed, and evaluated. In addition, as well as to characterize the agar phantom optically and acoustically, optical power measurements were also made under different LED lights at the phantom surface level. This study aimed to investigate the temperature and optical power effects of an LED therapy device on a well-characterized tissue-mimicking phantom prior to clinical application The results of this study indicate that the LED therapy device examined is safe and harmless for daily use, particularly in terms of temperature and related optical power effects.
17th IEEE International Symposium on Medical Measurements and Applications (IEEE MeMeA) -- JUN 22-24, 2022 -- Messina, ITALY
Keywords: LED Therapy Device; Agar; Tissue Phantom Optical Properties; Temperature Measurement; Optical Power Measurement; Statistical Analysis